2017
DOI: 10.3748/wjg.v23.i23.4222
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring mutations in the reverse transcriptase region of hepatitis B virus polymerase from treatment-naïve Korean patients infected with genotype C2

Abstract: AIMTo report naturally occurring mutations in the reverse transcriptase region (RT) of hepatitis B virus (HBV) polymerase from treatment naïve Korean chronic patients infected with genotype C2.METHODSHere, full-length HBV reverse transcriptase RT sequences were amplified and sequenced from 131 treatment naïve Korean patients chronically infected with hepatitis B genotype C2. The patients had two distinct clinical statuses: 59 patients with chronic hepatitis (CH) and 72 patients with hepatocellular carcinoma (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 51 publications
5
50
0
Order By: Relevance
“…The mutations rtA181T/V, rtM204I, and rtM204V also cause the simultaneous HBsAg mutations, sW172 stop, sW196S/L/Stop, and sI195M, respectively[ 17 , 72 ] (Table 1 ). Our literature based pooled incidence data showed that of primary drug resistance mutations, M204I/V is the most frequently encountered in treatment-naïve patients[ 14 , 28 , 33 ] (5.89%), which was far more than the pooled mutation rate of rtA181T/V, rtS202C/G/I and rtN236T (incidence: 1.16%, 0.85% and 0.81%, respectively). Mutation of rtI169T (0.12%), rtT184G (0.06%), rtA194T (0.07%), and rtM250V/L (0.20%) had a very low pooled incidence (Figure 1 ).…”
Section: Distribution Of Preexisting Hbv Nar Mutations In Samples Fromentioning
confidence: 94%
See 4 more Smart Citations
“…The mutations rtA181T/V, rtM204I, and rtM204V also cause the simultaneous HBsAg mutations, sW172 stop, sW196S/L/Stop, and sI195M, respectively[ 17 , 72 ] (Table 1 ). Our literature based pooled incidence data showed that of primary drug resistance mutations, M204I/V is the most frequently encountered in treatment-naïve patients[ 14 , 28 , 33 ] (5.89%), which was far more than the pooled mutation rate of rtA181T/V, rtS202C/G/I and rtN236T (incidence: 1.16%, 0.85% and 0.81%, respectively). Mutation of rtI169T (0.12%), rtT184G (0.06%), rtA194T (0.07%), and rtM250V/L (0.20%) had a very low pooled incidence (Figure 1 ).…”
Section: Distribution Of Preexisting Hbv Nar Mutations In Samples Fromentioning
confidence: 94%
“…Among the 50 studies, 36[ 12 , 20 , 21 , 32 - 58 , 60 - 65 ] used direct PCR sequencing methods, 11[ 22 - 28 , 59 , 66 - 68 ] used the INNO-LiPA line assay, and 3[ 29 - 31 ] detected RT mutations by ultra-deep pyrosequencing (UDPS). Seventeen articles[ 21 , 26 , 27 , 30 , 31 , 34 , 35 , 37 - 39 , 42 , 43 , 46 - 48 , 53 , 58 ] included treatment-naïve patients infected with genotypes B and C, one study[ 32 ] with genotypes A and D, eleven studies[ 22 , 28 , 29 , 36 , 50 , 51 , 55 , 56 , 60 , 63 , 68 ] with genotype D, one study[ 33 ] with genotype C, and fifteen studies[ 20 , 23 - 25 , 40 , 41 , 44 , 45 , 52 , 54 , 57 , 61 , 64 , 65 , 67 ] with more than three genotypes ( e.g ., A, C, and D or A, B, C, and D). In five studies, genotypes of patients were not mentioned.…”
Section: Distribution Of Preexisting Hbv Nar Mutations In Samples Fromentioning
confidence: 99%
See 3 more Smart Citations